2006
DOI: 10.1007/s11244-006-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

An overview: Comparative kinetic behaviour of Pt, Rh and Pd in the NO + CO and NO + H2 reactions

Abstract: This paper reports a comparative kinetic investigation of the overall reduction of NO in the presence of CO or H 2 over supported Pt-, Rh-and Pd-based catalysts. Different activity sequences have been established for the NO+H 2 reaction . It was found that both reactions differ from the rate determining step usually ascribed to the dissociation of chemisorbed NO molecules. The rate enhancement observed for the NO+H 2 reaction has been mainly related to the involvement of a dissociation step of chemisorbed NO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 55 publications
5
95
1
1
Order By: Relevance
“…No activation energies are presented for the 100% Pd nanocrystals due to extremely low turnover frequencies for all products in these reaction conditions. These results compare relatively well to previous studies on Rh and Pd nanoparticle catalysts, such as studies by Granger et al, who found higher turnover rates and activation energies on Rh/Al 2 O 3 catalysts as compared to Pd/Al 2 O 3 catalysts [16]. No synergism was observed in these conditions with the Rh 1-x Pd x nanocrystals.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No activation energies are presented for the 100% Pd nanocrystals due to extremely low turnover frequencies for all products in these reaction conditions. These results compare relatively well to previous studies on Rh and Pd nanoparticle catalysts, such as studies by Granger et al, who found higher turnover rates and activation energies on Rh/Al 2 O 3 catalysts as compared to Pd/Al 2 O 3 catalysts [16]. No synergism was observed in these conditions with the Rh 1-x Pd x nanocrystals.…”
Section: Resultssupporting
confidence: 90%
“…Rhodium is acknowledged to be the best catalyst for this reaction, with intense efforts devoted to understanding its behavior [3][4][5][6][7][8][9][10][11][12][13]. However, in recent years much research has also been aimed at understanding the role of Pd in the reaction [1][2][3][14][15][16][17][18][19] because of the relatively high cost of rhodium catalysts, palladium's improved resistance to sintering, and because new improvements in gasoline purification have helped reduce the significance of previous problems with Pd site poisoning by sulfur and lead [15]. Pd has been found to have lower activity than Rh for the reaction of NO with CO [16] and has also been shown to suffer from deactivation [14].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction proceeds much faster on Rh than on Pd or Pt [12] and is known to be structure sensitive on Rh single crystals [13]. The products of the reaction are CO 2 at all temperatures, N 2 O primarily (*75%) at the lower (\320°C) temperatures investigated in this study, and N 2 primarily at higher temperatures ([320°C) [12].…”
Section: Introductionmentioning
confidence: 65%
“…The reaction proceeds much faster on Rh than on Pd or Pt [12] and is known to be structure sensitive on Rh single crystals [13]. The products of the reaction are CO 2 at all temperatures, N 2 O primarily (*75%) at the lower (\320°C) temperatures investigated in this study, and N 2 primarily at higher temperatures ([320°C) [12]. Although many mechanisms have been proposed for this reaction [14][15][16][17][18][19][20], it remains an open area of investigation [21,22] due to its enormous complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Pd can catalyze the reduction of NO to N 2 , in addition to its activity for hydrocarbon and CO oxidation. [5][6][7][8][9][10][11] However, in the presence of hydrocarbons, the NO reducing capacity of Pd is lower than that reported for Rh-based catalysts. 8,12 In order to overcome this problem while employing relatively inexpensive metals, bimetallic Pd-Mo and Pd-W catalysts have been proposed.…”
Section: Introductionmentioning
confidence: 83%